Body composition, strength static and isokinetic, and bone health: comparative study between active adults and amateur soccer players - Tavares,Óscar M. (2019)
ABSTRACT Objective: To compare tissue composition, total and regional bone mineral content and bone mineral density, static hand grip and knee joint isokinetic strength between amateur soccer players and Control Group. Methods: Cross-sectional study. Air displacement plethysmography was used to estimate body volume and, in turn, density. Body composition, bone mineral content and bone mineral density were assessed for the whole body and at standardized regions using dual energy X-ray absorptiometry. Static grip strength was assessed with an adjustable dynamometer, and peak torque derived from isokinetic strength dynamometer (concentric muscular knee actions at 60°/s). Magnitude of the differences between groups was examined using d-Cohen. Results: Compared to healthy active adults, soccer players showed larger values of whole body bone mineral content (+651g; d=1.60; p<0.01). In addition, differences between groups were large for whole body bone mineral density (d=1.20 to 1.90; p<0.01): lumbar spine, i.e. L1-L4 (+19.4%), upper limbs (+8.6%) and lower limbs (+16.8%). Soccer players attained larger mean values in strength test given by static hand grip protocol (+5.6kg, d=0.99; p<0.01). Conclusion: Soccer adequately regulates body composition and is associated better bone health parameters (bone mineral content and density at whole-body and at particular sites exposed to mechanical loadings).